Multiple plastic biliary stent placement in the management of large and multiple choledochal stones: single center experience and review of the literature - Bektaş, Hasan (Wideochir Inne Tech Maloinwazyjne, 2017)
INTRODUCTION: Endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy is the first step treatment modality of choledocholithiasis. In spite of an extended sphincterotomy, 10–15% of complex choledochal stones (larger than 15 mm and/or more than 3 stones) cannot be removed and recurrent ERCP procedures may be needed. AIM: To evaluate the role and efficiency of multiple biliary stent application in the treatment of large and multiple choledochal stones. MATERIAL AND METHODS: Patients with complex choledochal stones and patients with inadequate choledochal clearance during ERCP were included in the study. The study group was divided into 2 groups as the placement of single (n = 27 patients) or multiple stents (n = 58 patients). After a mean time interval of 21 days (10–28), the ERCP procedure was tried for the second time and a stent was placed in case of recurrence. RESULTS: Successful biliary drainage was provided in both groups. The decrease in the longitudinal or transverse size of the stones after stent placement was found to be statistically significant in both groups (p = 0.001). Cholestatic enzymes (alkaline phosphatase (ALP), γ-glutamyltransferase (GGT)) and bilirubin levels decreased significantly in both groups following stenting (p = 0.001). Additionally, multiple stents functioned as a bridge starting from the first ERCP to full clearance in patients with large and multiple stones which could not be removed at once and saved them from the possible morbidities of an invasive operation. CONCLUSIONS: Endoscopic multiple biliary stent placement should be preferred in the treatment of patients with complex choledochal stones and high rates of co-morbidity, as a safe alternative to surgery.